Efektivitas Tutupan Vegetasi dalam Mereduksi Emisi Gas Rumah Kaca di RW 08 Gunung Anyar Tambak Surabaya - Abdul Rochim, Jihan Nazifa; Muhammad Faisal Fadhil (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Vegetation cover plays a vital role in climate change mitigation by absorbing atmospheric carbon dioxide (CO₂) through natural photosynthetic processes. This study assesses the effectiveness of vegetation cover in reducing greenhouse gas (GHG) emissions in RW 08, Gunung Anyar Tambak Sub-district, Surabaya. Data were collected through vegetation surveys and carbon stock calculations using allometric equations and referring to SNI 7724:2019. The results show that the total GHG emissions of 4,836.4 tons CO₂e/year (from a population of 2,140 with 2.26 tons CO₂e per capita) are still lower than the existing vegetation’s carbon sequestration capacity of 7,267.9 tons CO₂e/year. However, with a projected population growth of 0.82% per year, emissions are expected to surpass sequestration capacity by 2075, reaching 7,274.94 tons CO₂e/year. To prevent a shift to carbon deficit status, the study recommends planting high carbon-sequestering species such as Pongamia pinnata and Albizia chinensis. Those types of tress are chosen due to their properties such as high carbon sequestering, low maintenance, non-invasive, and adaptive to the urban conditions.